The Influence of Mobile Banking Innovation and Fee-Based Income on the Value of Banking Firms - Setiyono, Taufiq Andre; Setyowati, Widhy; Nurjanah, Wahdinii Widi (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
In today's world, banks are all about making life easier for their customers through technology. But shifting from traditional systems to these modern, innovative solutions isn't always a walk in the park. For banks to thrive in this competitive environment, they need to dive into digital transformation, like developing mobile banking apps and boosting fee-based income. This study looks at how these mobile banking innovations and fee-based income affect the value of banking firms on the Indonesia Stock Exchange (IDX) between 2021 and 2023. With 57 banks on the IDX as our study group, we used purposive sampling to pick our samples and multiple linear regression analysis with SPSS as our tool. The results show that mobile banking doesn't significantly impact the value of banking firms, but fee-based income does have a positive impact.